Outcomes and inflammation changes in different types of immunocompromised patients with critically ill COVID-19 admitted to ICU: a national multicenter study - Chunyan Li; Hangyong He; Yuqiong Wang; Linna Huang; Ziying Chen; Qi Zhang; Ying Cai; Tianshu Zhai; Xiaojing Wu; Qingyuan Zhan (BMC Pulmonary Medicine)
Abstract Background Immunocompromised patients face higher risks of Severe Acute Respiratory Syndrome Coronavirus 2 infection and co-infections, leading to a possibility of high disease severity and poor outcomes. Conversely, immunosuppression can mitigate the excessive inflammatory response induced by the virus, potentially reducing disease severity. This study aims to investigate the prognostic differences and early inflammatory response characteristics in various types of immunocompromised patients with severe coronavirus disease 2019 (COVID-19) admitted to intensive care unit (ICU), summarize their clinical features, and explore potential mechanisms. Methods A retrospective analysis was conducted on critically ill COVID-19 patients admitted to the ICU of 59 medical centers in mainland China during the Omicron outbreak from November 2022 to February 2023. Patients were categorized into two groups based on their immunosuppression status: immunocompromised and immunocompetent. Immunocompromised patients were further subdivided by etiology into cancer patients, solid organ transplant (SOT) patients, and other immunocompromised groups, with immunocompetent patients serving as controls. The mortality rates, respiratory support, complications, and early inflammatory cytokine dynamics upon ICU admission among different populations were analyzed. Results A total of 2030 critically ill COVID-19 patients admitted to ICU were included, with 242 in the immunocompromised group and 1788 in the immunocompetent group. Cancer patients had a higher median age of 69 years (IQR 59, 77), while SOT patients were generally younger and had less severe illness upon ICU admission, with a median APACHE II score of 12.0 (IQR 8.0, 20.0). Cancer patients had a twofold increased risk of death (OR = 2.02, 95% CI 1.18–3.46, P = 0.010) compared to immunocompetent patients. SOT and cancer patients exhibited higher C-reactive protein and serum ferritin levels than the immunocompetent group in their early days of ICU admission. The CD8+ T cells dynamics were inversely correlated in cancer and SOT patients, with Interleukin-6 levels consistently lower in the SOT group compared to both immunocompetent and cancer patients. Conclusion Critically ill COVID-19 patients admitted to the ICU exhibit distinct clinical outcomes based on their immunosuppression status, with cancer patients facing the highest mortality rate due to variations in inflammatory responses linked to their immunosuppression mechanisms. Monitoring dynamic changes in inflammatory markers and immune cells, particularly CD8+ T lymphocytes and IL-6, may offer valuable prognostic insights for these patients.